Learn more about

Refine search

Results (displaying matches 1-50 of 393) Next

Label Class Equation Sato-Tate \(\overline{\Q}\)-simple \(\GL_2\) Rank*
464.a.464.1 464.a \(y^2 + (x + 1)y = -x^6 - 2x^5 - 2x^4 - x^3\) $\mathrm{USp}(4)$ 0
472.a.60416.1 472.a \(y^2 + (x + 1)y = 8x^5 + 5x^4 + 4x^3 + 2x^2\) $\mathrm{USp}(4)$ 0
691.a.691.1 691.a \(y^2 + (x + 1)y = x^5 - x^3 - x^2\) $\mathrm{USp}(4)$ 0
709.a.709.1 709.a \(y^2 + xy = x^5 - 2x^2 + x\) $\mathrm{USp}(4)$ 0
720.a.6480.1 720.a \(y^2 + (x^3 + x)y = 2x^4 + 7x^2 + 5\) $G_{3,3}$ 0
807.a.2421.1 807.a \(y^2 + (x^3 + x)y = x^5 - 2x^3 - x^2 + 2x - 1\) $\mathrm{USp}(4)$ 0
832.a.832.1 832.a \(y^2 + (x^3 + x)y = x^5 - x^3 + x^2 + 2x - 1\) $\mathrm{USp}(4)$ 0
834.a.1668.1 834.a \(y^2 + (x^3 + 1)y = -x^2 + x - 1\) $\mathrm{USp}(4)$ 0
847.c.9317.1 847.c \(y^2 + (x^3 + x^2)y = x^4 + x^3 - x - 2\) $\mathrm{USp}(4)$ 0
862.a.862.1 862.a \(y^2 + (x^3 + 1)y = x^5 - 2x^4 - 7x^3 + 7x^2 + 2x + 5\) $\mathrm{USp}(4)$ 0
882.a.302526.1 882.a \(y^2 + (x^3 + 1)y = x^5 - 2x^4 - 5x^3 + 11x^2 - 12x + 5\) $G_{3,3}$ 0
909.a.909.1 909.a \(y^2 + (x^3 + x)y = -x^4 + x^2 - x\) $\mathrm{USp}(4)$ 0
925.a.925.1 925.a \(y^2 + (x + 1)y = -x^5 + 2x^4 - x^3 - x^2\) $\mathrm{USp}(4)$ 0
930.a.930.1 930.a \(y^2 + (x^2 + x)y = -x^5 - 7x^4 + 37x^2 - 45x + 15\) $G_{3,3}$ 0
936.a.1872.1 936.a \(y^2 + (x^3 + x)y = -x^6 - 9x^4 - 32x^2 - 39\) $G_{3,3}$ 0
960.a.245760.1 960.a \(y^2 = 2x^5 + x^4 + 4x^3 + x^2 + 2x\) $G_{3,3}$ 0
960.a.368640.1 960.a \(y^2 = x^5 + 13x^4 + 44x^3 + 13x^2 + x\) $G_{3,3}$ 0
960.a.983040.1 960.a \(y^2 = x^5 - 2x^4 - x^3 - 2x^2 + x\) $G_{3,3}$ 0
990.a.8910.1 990.a \(y^2 + (x^2 + x)y = 3x^5 + 4x^4 + 7x^3 + 4x^2 + 3x\) $G_{3,3}$ 0
997.a.997.1 997.a \(y^2 + xy = x^5 - 8x^4 + 16x^3 - x\) $\mathrm{USp}(4)$ 0
997.a.997.2 997.a \(y^2 + (x + 1)y = x^5 + x^4\) $\mathrm{USp}(4)$ 0
1050.a.131250.1 1050.a \(y^2 + (x^2 + x)y = 3x^6 + 8x^5 + 15x^4 + 17x^3 + 15x^2 + 8x + 3\) $G_{3,3}$ 0
1051.b.1051.1 1051.b \(y^2 + (x + 1)y = -x^5 - x^4\) $\mathrm{USp}(4)$ 0
1123.a.1123.1 1123.a \(y^2 + (x^3 + x)y = -x^4 - x^2 - x\) $\mathrm{USp}(4)$ 0
1147.a.35557.1 1147.a \(y^2 + xy = x^5 + 8x^4 + 18x^3 + 8x^2 + x\) $\mathrm{USp}(4)$ 0
1152.a.147456.1 1152.a \(y^2 = x^6 - 2x^4 + 2x^2 - 1\) $J(E_1)$ 0
1176.a.2352.1 1176.a \(y^2 + (x^3 + x)y = x^4 + 3x^2 + 3\) $G_{3,3}$ 0
1184.a.2368.1 1184.a \(y^2 + y = 2x^5 + x^4 + x^2 + x\) $\mathrm{USp}(4)$ 0
1184.a.606208.2 1184.a \(y^2 = x^6 - 2x^5 + 5x^4 - 4x^3 + 6x^2 - 2x + 2\) $\mathrm{USp}(4)$ 0
1225.a.6125.1 1225.a \(y^2 + (x^3 + x^2)y = 2x^3 + x^2 + x + 2\) $G_{3,3}$ 0
1309.a.9163.1 1309.a \(y^2 + (x^2 + 1)y = 7x^5 - x^4 - 5x^3 - x^2 + x\) $\mathrm{USp}(4)$ 0
1320.a.2640.1 1320.a \(y^2 + (x^3 + x)y = -x^6 + 9x^4 - 40x^2 + 55\) $G_{3,3}$ 0
1344.a.4032.1 1344.a \(y^2 + xy = -x^6 - 12x^4 - 48x^2 - 63\) $N(G_{1,3})$ 0
1344.a.4032.2 1344.a \(y^2 + xy = -x^6 + 12x^4 - 48x^2 + 63\) $N(G_{1,3})$ 0
1344.b.172032.1 1344.b \(y^2 = x^5 - 11x^4 + 32x^3 - 11x^2 + x\) $G_{3,3}$ 0
1376.a.2752.1 1376.a \(y^2 + y = 2x^5 + 3x^4 - 2x^2\) $\mathrm{USp}(4)$ 0
1408.b.180224.1 1408.b \(y^2 = 2x^5 + 2x^4 + 4x^3 + 3x^2 + 2x + 1\) $\mathrm{USp}(4)$ 0
1408.b.720896.1 1408.b \(y^2 + y = 4x^5 + 17x^4 - 8x^3 - 3x^2 + x\) $\mathrm{USp}(4)$ 0
1408.b.720896.2 1408.b \(y^2 = x^5 + 2x^3 - 4x^2 + x\) $\mathrm{USp}(4)$ 0
1470.a.2940.1 1470.a \(y^2 + (x^2 + x)y = -x^6 + 2x^5 - 5x^4 + 4x^3 - 5x^2 + 2x - 1\) $G_{3,3}$ 0
1472.a.5888.1 1472.a \(y^2 = x^5 + x^4 - x^3 - 2x^2 - x\) $\mathrm{USp}(4)$ 0
1472.a.94208.2 1472.a \(y^2 + y = 4x^5 + x^4 + 4x^2 + 2x\) $\mathrm{USp}(4)$ 0
1534.a.3068.1 1534.a \(y^2 + (x^3 + 1)y = x^5 - 4x^3 - x^2 + 4x - 1\) $\mathrm{USp}(4)$ 0
1536.b.49152.2 1536.b \(y^2 + x^3y = 3x^4 + 11x^2 + 12\) $N(G_{1,3})$ 0
1536.c.98304.1 1536.c \(y^2 + y = 4x^6 - 12x^5 + 3x^4 + 14x^3 - 5x^2 - 4x + 1\) $N(G_{1,3})$ 0
1573.b.224939.1 1573.b \(y^2 + (x + 1)y = x^5 + x^4 - 5x^3 + 3x^2 - 1\) $\mathrm{USp}(4)$ 0
1584.a.684288.1 1584.a \(y^2 + (x^3 + x)y = -x^6 + 6x^4 - 17x^2 + 11\) $G_{3,3}$ 0
1656.a.804816.1 1656.a \(y^2 + xy = 2x^5 - 6x^4 + 13x^3 - 13x^2 + 9x\) $\mathrm{USp}(4)$ 0
1680.a.16800.1 1680.a \(y^2 + (x^3 + x)y = -x^6 - 18x^4 - 136x^2 - 350\) $G_{3,3}$ 0
1800.a.3600.1 1800.a \(y^2 + (x^3 + x)y = -x^4 + x^2 - 1\) $G_{3,3}$ 0
Next

Download all search results for